(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2025)
Microorganisms within the oral cavity exist in balance with one another and the host’s immune system, contributing to oral health. Disruption of this balance can result in microbial activity that leads to oral diseases and oral diseases are linked to microorganisms that exist in the oral cavity. Mouth contains one of the utmost complex in addition to various microorganism ecosystems in the human body. The oral microorganism contributes to maintaining homeostasis within the oral host. However, environmental, behavioral, or systemic changes can lead to ecological shifts in the balanced microbial community, leading to oral diseases including dental caries and periodontitis. These microorganisms exist in a balanced manner with each other and with the immune system of the organism, and thus this leads to maintaining oral health. However, any imbalance in this balance leads to the microorganisms living in the mouth becoming disease-causing. This review aims for survey the structure and dynamics of the mouth microorganism, the transition from commensalism to pathogenesis, diseases caused by microorganisms present in the mouth ,the relationship of these microorganisms to people with immune deficiency , current procedures to restore microbial balance. Understanding these dynamics can guide the development of targeted therapies for oral and systemic health.